2016
DOI: 10.1175/mwr-d-15-0370.1
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Analysis of the Relationship between Upper-Tropospheric Cold Low and Tropical Cyclone Track and Intensity Change over the Western North Pacific

Abstract: The geographical and temporal characteristics of upper-tropospheric cold low (UTCL) and their relationship to tropical cyclone (TC) track and intensity change over the western North Pacific (WNP) during 2000-12 are examined using the TC best track and global meteorological reanalysis data. An analysis of the two datasets shows that 73% of 346 TCs coexist with 345 UTCLs, and 21% of the latter coexist with TCs within an initial cutoff distance of 158. By selecting those coexisted systems within this distance, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…After TC genesis occurs, the role an upper-tropospheric PV anomaly plays in TC intensification is ambiguous. While troughs have been found to be unfavorable for the intensification of TCs in general (DeMaria et al 1993;Peirano et al 2016), some studies have documented cases of favorable TC-trough interactions (Molinari and Vollaro 1989;Hanley et al 2001;Leroux et al 2013;Wei et al 2016). The favorable mechanisms for TC intensification in the presence of an uppertropospheric trough include eddy flux convergence of angular momentum (EFC) (Molinari and Vollaro 1989), eddy fluxes of PV (Leroux et al 2013), and PV superposition (Molinari et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…After TC genesis occurs, the role an upper-tropospheric PV anomaly plays in TC intensification is ambiguous. While troughs have been found to be unfavorable for the intensification of TCs in general (DeMaria et al 1993;Peirano et al 2016), some studies have documented cases of favorable TC-trough interactions (Molinari and Vollaro 1989;Hanley et al 2001;Leroux et al 2013;Wei et al 2016). The favorable mechanisms for TC intensification in the presence of an uppertropospheric trough include eddy flux convergence of angular momentum (EFC) (Molinari and Vollaro 1989), eddy fluxes of PV (Leroux et al 2013), and PV superposition (Molinari et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…These works suggest that the TC track depends on both of low-frequency flows associated with the MG and the TC vortex itself. Wei et al (2016) statistically investigated the relationship between the upper tropospheric cold low (UTCL) and the TC tracks over the WNP during 2000-2012.…”
Section: Large Scale Featuresmentioning
confidence: 99%
“…The quantity with a plus in parentheses shows a significant increase in the mean directional change of the TCs in the shaded distance range over the corresponding WNP climatology. (afterWei et al 2016)…”
mentioning
confidence: 99%
“…Another previous study by Wei et al (2016) investigated changes in TC track and intensity due to UCLs over the WNP during the 13 years from 2000 to 2012. The results of this study showed that 73 % of TCs coexisted with UCLs that included an upper tropospheric low originating from TUTT cells and cutoff lows in the mid-latitudes, and 44 % of the TCs had interacted with UCLs during their lifetimes.…”
Section: Introductionmentioning
confidence: 99%
“…Although Wei et al (2016) have revealed the statistical characteristics of TCs interacting with UCLs throughout the TC lifecycle, few have examined the characteristics of TCs where TCG was influenced by UCLs in the northwest quadrant of the TCG region (hereinafter referred to as UL-TCs). In addition, the analysis period of the statistical study described above was only 4 years, and annual changes in UL-TCs were not investigated.…”
Section: Introductionmentioning
confidence: 99%